ECG morphology of premature ventricular contractions predicts the presence of myocardial fibrotic substrate on cardiac magnetic resonance imaging in patients undergoing ablation. (1st September 2017) - Oebel, Sabrina; Dinov, Borislav; Arya, Arash; Hilbert, Sebastian; Sommer, Philipp; Bollmann, Andreas; Hindricks, Gerhard; Paetsch, Ingo; Jahnke, Cosima
Abstract: Background: The most likely origin of premature ventricular contractions (PVCs) may be deduced from surface electrocardiogram (ECG) analysis while planning an electrophysiological study (EPS). Apart from purely benign forms of increased ventricular ectopy, myocardial substrate (e.g., regional fibrosis) may be present in certain cases, which will significantly impact the ablation approach. Cardiac magnetic resonance (CMR) imaging can reliably identify fibrotic target lesions and, hence, may assist in adequate patient selection and procedural planning. Methods and results: We analyzed 101 patients (59% males, mean age 57.15 ± 15.5 years, mean PVC count 19, 801 ± 14, 021 per 24 hours) referred for ablation of PVCs. The CMR (1.5T, Philips Ingenia, Best, The Netherlands) protocol included cine and three‐dimensional‐delayed enhancement imaging using standard cardiac geometries. On surface, ECG right bundle branch block (RBBB) morphology was present in 43% of patients. Twenty‐one patients showed the fibrotic substrate on CMR. On univariate analysis, both RBBB morphology (P < 0.001) and presence of multiple PVC morphologies (≥2) significantly predicted the presence of fibrotic substrate (P = 0.01), which various baseline characteristics including left ventricular ejection fraction (45.7 ± 12.6% vs. 50.6 ± 11.0%, P = 0.08) failed to do. CMR‐identified fibrosis was associated with the site of origin of the clinical PVCs during EPS and was successfully treated by radiofrequency ablation in 93% (PVC reduction >95%). Conclusion: In patients with RBBB morphology and/or multiple PVC patterns, CMR imaging before ablation may be helpful due to the increased prevalence of fibrotic lesions with regard to patient stratification and periprocedural management.